INTEGRATING REMOTE SENSING DATA WITH HYDROTHERMAL ALTERATION MAPPING AND GEOCHEMICAL CHARACTERISTICS OF PRECAMBRIAN ROCKS ACROSS MAMBILLA PLATEAU, NORTHEASTERN, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Mineral exploration must include the mapping of hydrothermally altered regions, which are typically connected to mineralization. This study presents a strategy for integrating remote sensing data with the geochemical characteristics of Precambrian rocks from the Mambilla Plateau in northern Nigeria. Tectonically, the lineaments were fractures with the following orientations: NE-SW, NW-SE, ENE-WSW, and N-S. The distinct spectral reflectance and absorption properties of remotely sensed Landsat 8 data in the visible, near-infrared, shortwave-infrared, and thermal infrared portions of the electromagnetic spectrum were exploited in various digital image processing approaches. Mapping hydrothermal alteration minerals was done effectively and efficiently using band ratios (red/blue, SWIR 2/NIR, SWIR 1/NIR), spectral band combinations (Kaufmann and Sabins ratios), and principal component analysis. Ferric, phyllic, propylitic, and argillic iron all underwent changes as a result of hydrothermal alteration. Regional metamorphism also resulted in important alteration processes such as epidotization, sericitization, muscovititization, kaolinitization, and chloritization. Geochemically, on average, the Al2O3, SiO2, Fe2O3, CaO, MgO, K2O, Na2O, Li2O content are 12.04 %; 54.83%; 4.76%,  7.16%,  3.02%, 10.22%, 4.53%, 1.35%  while MnO, P2O5  and TiO2 are less than 1%. The average base metal composition revealed that 60% of them had positive anomalies, which indicate mineralization, and 40% had negative anomalies. About 50% of the samples had positive anomalies, which indicated strong potential for harbouring mineralization based on the makeup of trace elements. Geochemical studies revealed the presence of lithium, titanium, and silica oxides in substantial concentrations. The local mineralization is governed by structural factors.
Keywords: Remote sensing datasets; Hydrothermal alteration mapping; Geochemical characteristics; Mineralization potentials; Precambrian rocks